Increased Algal Symbiont Density Reduces Host Immunity in a Threatened Caribbean Coral Species, Orbicella faveolata - Fuess, Lauren E.; Palacio-Castro, Ana M.; Butler, Caleb C.; Baker, Andrew C.; Mydlarz, Laura D. (Frontiers in Ecology and Evolution, 2020)
Scleractinian corals are the principal builders of coral reefs. These megadiverse ecosystems are declining due to coral mortality from a variety of stressors, including disease. Corals are dependent upon symbiotic dinoflagellates in the family Symbiodiniaceae for phototrophic contributions to their energy budgets. However, suppression of host immunity may be necessary to maintain these intracellular symbioses. To explore the consequences of symbiosis on host immunity, we manipulated symbiont density by increasing nitrogen availability. Replicate cores from four colonies of the Caribbean coral, Orbicella faveolata, were reared in seawater treated with ammonium for one month to increase symbiont density. Corals were then immune-stimulated using lipopolysaccharide and poly I:C. Gene expression was analyzed using RNAseq and symbiont density was quantified (as symbiont:host cell ratio) using quantitative PCR (qPCR). Ammonium treatment had limited positive effects on host immunity. In contrast, increases in symbiont density had large negative effects on host expression of immune-related transcripts. These results suggest links between nutrient enrichment and coral disease may be the result of the effect of increased symbiont density on host immunity, rather than the direct effect of the nutrients. Further study of the trade-offs between symbiont density and immunity may help understand how decreasing water quality and increasing disease will shape future reef communities.